Peran Organizational Citizenship Behavior sebagai Variabel Mediasi Pengaruh Emotional Intelligence terhadap Kinerja di Fakultas Ekonomi Universitas Negeri Surabaya - Fatmawati, Inas Khildah; Indawati, Nurul (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
The purpose of this study is to analyze the effect of emotional intelligence on performance through organizational citizenship behavior. Respondents in this study were lecturers at the Faculty of Economics, Universitas Negeri Surabaya and 56 samples were obtained for analysis. Data analysis technique used is a Partial Least Square with SmartPLS 3.0 software.The results show that there is a positive and significant effect between emotional intelligence with performance, emotional intelligence with organizational citizenship behavior, OCB with performance, and emotional intelligence with performance through OCB.